Optimization of fertilizer nitrogen at varying levels of life-saving irrigation water for mustard (Brassica juncea) under semi-arid Inceptisols - Nema, A K; Sankar, G.R Maruthi; Chauhan, S.P.S (The Indian Journal of Agricultural Sciences, 2008)
Field experiments were conducted with Indian mustard [Brassica juncea (L.) Czernj & Cosson] during winter (rabi) seasons of 2003, 2004 and 2005 under semi-arid Inceptisols at Agra. The treatments were a complete factorial of 4 levels of N, viz 0, 40, 80 and 120 kg/ha applied at sowing and 4 levels of irrigation provided at different stages (control, 8 cm depth at 50% flowering, 8 cm depth at 50% siliqua formation) and 4 cm depth at 50% flowering + 4 cm depth at 50% siliqua formation. Irrigation and fertilizer N alone and in combination caused significant effect on mustard yield in each season and also pooled over 3 seasons. A maximum yield response of 800 kg/ha with a response ratio of 10 kg/kg fertilizer application were attained with an application of 80 kg N/ha and 4 cm depth at 50% flowering + 4 cm depth at 50% siliqua formation stages. The mustard yield was significantly and positively correlated with fertilizer N applied as basal and irrigation provided at 50% flowering and 50% siliqua formation stages in all the 3 seasons. A regression model of yield was calibrated as a function of fertilizer N and irrigation gave a significant predictability of 0.96 and an expected yield in the range of 1 263 kg/ha under control to 2 757 kg/ha under basal application of 80 kg N/ha together with an irrigation of 4 cm depth at 50% flowering + 4 cm depth at 50% siliqua formation stages. Among different treatment combinations, basal application of 80 kg N/ha together with irrigation of 4 cm depth at 50% flowering + 4 cm depth at 50% siliqua formation stage had a maximum sustainable yield index of 95.2% compared to a minimum of 49.1% under the control. Using regression model of yield, the derived optimum fertilizer N ranged from 72 to 78 kg/ha for attaining maximum yield and 68 to 73 kg/ha for attaining economic yield of mustard at a varying level of irrigation of 0 to 8 cm depth provided at 50% flowering and 50% siliqua formation stages in the study.